The Residential Segregation of the Middle Eastern and North African and South Asian Populations from the White Population in U.S. Metropolitan Areas, 2012–2016 - Sevsem Cicek-Okay; Samantha Friedman (Social Sciences)
We examine the residential segregation of the Middle Eastern and North African (MENA) population, South and East Asian people, and Black from white people in the U.S. Using data from the 2012–2016 American Community Survey (ACS) and the 2012–2016 Integrated Public Use Microdata Sample (IPUMS) at the metropolitan level, descriptive analyses of segregation reveal that Black–white segregation is significantly greater than the segregation of MENA and East Asian people from white people. South Asian–white segregation is higher than Black–white segregation, but the difference is not statistically significant. Multivariate analyses of average dissimilarity indices show that relative to Black–white segregation, MENA–white, South Asian–white, and East Asian–white segregation are not significantly different after controlling for relevant variables. The results for the isolation index also follow a similar pattern. While MENA and both Asian ancestry groups are significantly less isolated than Black people in the unadjusted results, the differences in average isolation indices between Black people and these groups disappear after controlling for relevant characteristics. The results suggest evidence that supports these hypotheses in terms of spatial assimilation.